Caregiver Burden of Advance Lung Cancer Patient: a concept analysis - Pribadi, Dimas Ria Angga; Lin, Hung Ru (South East Asia Nursing Research, 2022)
Caregiver burden is commonly used in nursing literature, however, a study exploring the caregiver burden of an advanced lung cancer patient has not yet been clearly defined. Therefore, this study Aims to develop an operational definition and analyze the attributes, antecedents and consequents of the theoretical concept of caregiver burden of advanced lung cancer. An electronic search from four different sources, such as online databases (PubMed, CINAHL (Cummulative Index for Nursing and Allied Health) Plus with Full Text, Chochrane Library, Google Scholar), journal articles, dictionaries and official health websites (both government and non-government). The paper adopted the framework by Walker and Advant. The attributes, antecedents and consequents of the concept were identified. The three attributes of caregiver burden were identified as Low Self- Efficacy, Multifaced Strain, and Overload. The antecedents included Caregiver’s characteristics, Health status, Insufficient financial resources, and social support. The consequences of the caregiver’s burden resulted in negative change, including decreased quality of Life, Health function, and psychological problems. A clear definition of caregiver burden was developed. The finding of this concept analysis can be used in Nursing practice, education and administration